Of Tongues and Men: A Review of Morphological Evidence for the Evolution of Language. Issue 1 (29th January 2018) - Albessard-Ball, Lou; Balzeau, Antoine
Abstract: Of the characteristics of the species Homo sapiens relative to other living animals, the use of articulated language is among the most striking. Because it implies—and allows for—complex social relationships and cognitive processes, the emergence of articulated language during hominin evolution is regarded as one of the most important steps in becoming human. Other living species have evolved complex vocalisations (e.g. songbirds) or can be trained to respond to spoken commands (e.g. dogs) and even to answer using special keyboards or sign language (e.g. great apes), but none have evolved articulated speech, and none can be taught how to talk. Tracking the emergence of language and determining which fossil hominin species used a full-fledged articulated language and which did not are somewhat of a challenge. For palaeoanthropologists and prehistorians, the timing and nature of the emergence of language—gradual or sudden, early or late in evolution—represent crucial (but missing) data when trying to interpret behaviours evidenced by the archaeological record or to define which hominins are 'human'. A wealth of morphological and archaeological data are examined in order to put together enough clues to answer the question of when and in which species speech first evolved. Lines of enquiry include the evolution of the neural circuitry used by H. sapiens to produce and process speech, the anatomical specialisations which allow them to discriminate and articulate sounds, and early evidence for complex, planned behaviours and symbolic thought. This indirect evidence does not bring definitive answers about the emergence of language in the hominin evolutionary bush but illustrates that we should rethink what defines H. sapiens and be more cautious—or scientifically more rigorous—about what makes us supposedly unique.